2017
DOI: 10.1016/j.celrep.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional Inhibition of Hsc70-4/HSPA8 Expression Leads to Synaptic Vesicle Cycling Defects in Multiple Models of ALS

Abstract: Summary Amyotrophic Lateral Sclerosis (ALS) is a synaptopathy accompanied by the presence of cytoplasmic aggregates containing TDP-43, an RNA binding protein linked to ~97% of ALS cases. Using a Drosophila model of ALS, we show that TDP-43 OE in motor neurons results in decreased expression of the Hsc70-4 chaperone at the neuromuscular junction (NMJ). Mechanistically, mutant TDP-43 sequesters hsc70-4 mRNA and impairs its translation. Expression of Hsc70-4’s ortholog, HSPA8 is also reduced in primary motor neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 77 publications
8
99
0
Order By: Relevance
“…Recently, an interesting mechanistic connection has been identified between ribostasis and proteostasis [15]. Using the same Drosophila model of ALS [35, 36] the authors identified hsc70-4 mRNA as a candidate target of mutant but not wild-type TDP-43 [15].…”
Section: Translational Alterations In Different Types Of Als and Als/ftdmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an interesting mechanistic connection has been identified between ribostasis and proteostasis [15]. Using the same Drosophila model of ALS [35, 36] the authors identified hsc70-4 mRNA as a candidate target of mutant but not wild-type TDP-43 [15].…”
Section: Translational Alterations In Different Types Of Als and Als/ftdmentioning
confidence: 99%
“…A similar post-transcriptional reduction was observed in C9 ALS fly and patient-derived motor neurons, although it remains to be determined whether this is caused by translation inhibition as was the case with TDP-43 models. Notably, restoration of Hsc70-4 through genetic overexpression mitigated ALS phenotypes in a variant-dependent manner suggesting that although both wild-type and mutant TDP-43 contribute to ALS pathogenesis, they do so through distinct mechanisms [15]. …”
Section: Translational Alterations In Different Types Of Als and Als/ftdmentioning
confidence: 99%
“…Indeed, under normal conditions, TDP-43 is required for preventing the downregulation of the microtubule stabilizing protein Futsch and maintain synaptic integrity (Godena et al, 2011; Romano et al, 2016). In disease, TDP-43 appears to cause toxicity by sequestering mRNAs and reducing their availability to the translation machinery as shown for futsch and hsc70-4 mRNAs (Coyne et al, 2014; Coyne et al, 2017a). Hsc70-4 is a chaperone required for synaptic vesicle cycling and its downregulation in TDP-43 proteinopathy provides a mechanistic explanation for synaptic dysfunction in ALS (Coyne et al, 2017a).…”
Section: Tdp-43 In Amyotrophic Lateral Sclerosis (Als)/fronto-tempmentioning
confidence: 99%
“…In disease, TDP-43 appears to cause toxicity by sequestering mRNAs and reducing their availability to the translation machinery as shown for futsch and hsc70-4 mRNAs (Coyne et al, 2014; Coyne et al, 2017a). Hsc70-4 is a chaperone required for synaptic vesicle cycling and its downregulation in TDP-43 proteinopathy provides a mechanistic explanation for synaptic dysfunction in ALS (Coyne et al, 2017a). In neuroblastoma cells, TDP-43 interacts directly with ribosomes via RACK1, which impacts translation globally and may have implications in disease (Russo et al, 2017).…”
Section: Tdp-43 In Amyotrophic Lateral Sclerosis (Als)/fronto-tempmentioning
confidence: 99%
See 1 more Smart Citation